Trasplantation of larynx and trachea: both a present and future option Trasplantes de la laringe y tráquea, una opción para el presente y el futuro - Francisco Martínez; Elmer Gaviria Rivera; Clara M. Casas; Alfonso White; Byron López; Fidel Cano; Luis Fernando Tintinago (Iatreia, 2004)
Lost functions of the larynx and the trachea may be restored by different means, but none of them is physiologic and patients are left with functional difficulties and self-esteem disorders that alter the quality of their lives. Transplantation of these organs is an useful alternative but certain basic requirements concerning revascularization, reinnervation and immunosupression should be fulfilled. The former has been achieved through the knowledge of vascular territories and the advances in surgical techniques. Difficulties for reinnervation have no yet been thoroughly overcome but tone can be achieved in the vocal folds and functionality may be obtained by manipulation of their position. Immunosupression is produced with cyclosporine which requirements were determined in experimental models. The main reason for carrying out these and other transplantations is to improve the quality of life of persons who have suffered the loss of an organ. A review is presented on important aspects that have to be taken into account when performing these transplantations. Las funciones perdidas de la laringe o la tráquea se pueden reemplazar de diferentes maneras; sin embargo, ninguna alternativa es fisiológica y los trasplantes quedan con dificultades funcionales y de autoestima que alteran la calidad de sus vidas, El Trasplante de estos órganos es una alternativa útil, pero deben cumplirse ciertos requisitos básicos en cuanto a la revascularización, la reinervación y la imunosupresión. El primero se logró con el conocimiento de los territorios vasculares y los avances en las técnicas quirúrgicas. Las dificultades para la reinervación todavía no se han superado totalmente, pero se puede lograr tono en los pliegues vocales y obtener funcionalidad manipulando su posición. la inmunosupresión se logra con ciclosporina cuyos requerimientos se definieron en modelos experimentales. La principal razón para hacer estos y otros trasplantes es mejorar la calidad de vida de las personas que han sufrido la pérdida de un órgano. Se presenta una revisión de aspectos importantes a tener en cuenta para llevar a cabo estos trasplantes.